Fine-Scale Plant Richness Mapping of the Andean Páramo According to Macroclimate - Peyre, Gwendolyn; Balslev, Henrik; Font, Xavier; Tello, J. Sebastián (Frontiers in Ecology and Evolution, 2019)
How the macroclimate conditions spatial patterns of plant diversity has been extensively studied in many systems and usually proven a strong relationship, however tropical mountains remain understudied. Because understanding primary drivers of diversity patterns in the Andean páramo is still in its infancy, we focused on evaluating the role of the current macroclimate in form of three complementary hypotheses, energy, seasonality and harshness, in explaining local variation of plant species richness. We relied on 1559 vegetation plots that offered a fine-scale outlook on real species assemblages due to community rules and species’ interactions with their surrounding environment, including climate. Generalized Least Squares (GLS) regression models provided insight on the significance of the different hypotheses in explaining local plant richness, but only the energy and seasonality hypotheses received partial support. The best model was then combined with spatial interpolation Kriging modelling techniques to project species richness for a standardized 25m2 plot throughout the entire páramo biogeographic province. We highlighted a North-South increase in richness with several species-rich areas, potential local biodiversity hotspots, independent of the general gradient: the Amotape-Huancabamba zone, Sangay and Cotacachi areas, and eastern Venezuelan Andes. Our endeavor to finely map local richness is the first effort predicting macroecological patterns in the emblematic Andean páramo and contributes novel biogeographic knowledge useful to further support in-depth research and conservation focus in the northern Andes.